Baseball basics - Lang, Jack Frederick (Prentice-Hall, Inc. Englewood Cliffs, New Jersey, 1981)
Discusses baseball history, rule changes, the fundamentals of various positions, team membership and management, and other related topics.
Includes index
Keywords: Baseball -- Juvenile Literature